Fabrication and electrochemical characterization of super-capacitor based on three-dimensional composite structure of graphene and a vertical array of carbon nanotubes. (September 2018) - Choi, Daniel; Yang, Eui-Hyeok; Gill, Waqas; Berndt, Aaron; Park, Jung-Rae; Ryu, Jong Eun
We have demonstrated a three-dimensional composite structure of graphene and carbon nanotubes as electrodes for super-capacitors. The goal of this study is to fabricate and test the vertically grown carbon nanotubes on the graphene layer acting as a spacer to avoid self-aggregation of the graphene layers while realizing high active surface area for high energy density, specific capacitance, and power density. A vertical array of carbon nanotubes on silicon substrates was grown by a low-pressure chemical vapor deposition process using anodized aluminum oxide nanoporous template fabricated on silicon substrates. Subsequently, a graphene layer was grown by another low-pressure chemical vapor deposition process on top of a vertical array of carbon nanotubes. The Raman spectra confirmed the successful growth of carbon nanotubes followed by the growth of high-quality graphene. The average measured capacitance of the three-dimensional composite structure of graphene-carbon nanotube was 780 µFcm −2 at 100 mVs −1 .